Factors Influencing Cecal Intubation Time during Retrograde Approach Single-Balloon Enteroscopy. (19th November 2014) - Ou, Tzu-Ming; Chen, Peng-Jen; Shih, Yu-Lueng; Wang, Meng-Ting; Huang, Hsin-Hung; Chang, Wei-Kuo; Hsieh, Tsai-Yuan; Huang, Tien-Yu
Abstract : Background and Aim . The predisposing factors for prolonged cecal intubation time (CIT) during colonoscopy have been well identified. However, the factors influencing CIT during retrograde SBE have not been addressed. The aim of this study was to determine the factors influencing CIT during retrograde SBE. Methods . We investigated patients who underwent retrograde SBE at a medical center from January 2011 to March 2014. The medical charts and SBE reports were reviewed. The patients' characteristics and procedure-associated data were recorded. These data were analyzed with univariate analysis as well as multivariate logistic regression analysis to identify the possible predisposing factors. Results . We enrolled 66 patients into this study. The median CIT was 17.4 minutes. With univariate analysis, there was no statistical difference in age, sex, BMI, or history of abdominal surgery, except for bowel preparation ( P = 0.021 ) . Multivariate logistic regression analysis showed that inadequate bowel preparation (odds ratio 30.2, 95% confidence interval 4.63–196.54; P < 0.001 ) was the independent predisposing factors for prolonged CIT during retrograde SBE. Conclusions . For experienced endoscopist, inadequate bowel preparation was the independent predisposing factor for prolonged CIT during retrograde SBE.